Effectiveness and Safety of Ustekinumab in Elderly Patients with Crohn's Disease: Real World Evidence From the ENEIDA Registry. (1st August 2022) - Casas-Deza, Diego; Lamuela-Calvo, Luis Javier; Gomollón, Fernando; Arbonés-Mainar, José Miguel; Caballol, Berta; Gisbert, Javier P; Rivero, Montserrat; Sánchez-Rodríguez, Eugenia; Arias García, Lara; Gutiérrez Casbas, Ana; Merino, Olga; Márquez, Lucía; et al.
Abstract: Background and Aims: Clinical trials and real-life studies with ustekinumab in Crohn's disease [CD] have revealed a good efficacy and safety profile. However, these data are scarcely available in elderly patients. Therefore, we aim to assess the effectiveness and safety of ustekinumab in elderly patients with CD. Methods: Elderly patients [>60 years old] from the prospectively maintained ENEIDA registry treated with ustekinumab due to CD were included. Every patient was matched with two controls under 60 years of age, according to anti-tumour necrosis factor use and smoking habit. Values for the Harvey–Bradshaw Index [HBI], endoscopic activity, C-reactive protein [CRP] and faecal calprotectin [FC] were recorded at baseline and at weeks 16, 32 and 54. Results: In total, 648 patients were included, 212 of whom were elderly. Effectiveness was similar between young and elderly patients during the follow-up. Steroid-free remission was similar at week 16 [54.6 vs 51.4%, p  = 0.20], 32 [53.0% vs 54.5%, p  = 0.26] and 54 [57.8% vs 51.1%, p  = 0.21]. Persistence of ustekinumab as maintenance therapy was similar in both age groups [log-rank test; p  = 0.91]. There was no difference in the rate of adverse effects [14.2% vs 11.2%, p  = 0.350], including severe infections [7.1% vs 7.3%, p  = 1.00], except for the occurrence of de novo neoplasms, which was higher in older patients [0.7% vs 4.3%, p  = 0.003]. Conclusions: Ustekinumab is as effective in elderly patients with CD as it is in non-elderly patients. The safety profile also seems to be similar except for a higher rate of de novo neoplasms, probably related to the age of the elderly patients.